1991
DOI: 10.1021/jo00026a004
|View full text |Cite
|
Sign up to set email alerts
|

An efficient asymmetric synthesis of 1-acyl-2-alkyl-1,2-dihydropyridines

Abstract: Two efficient chiral auxiliary mediated asymmetric syntheses of synthetically useful l-acyl-2-alkyl-1,2-dihydropyridines are described.For many years there has been considerable interest in the synthesis, synthetic utility, and biological activity of various dihydropyridines.1 The ability of an iV-acyl substituent to stabilize2 the dihydropyridine system has encouraged the use and study of 1-acyldihydropyridines as synthetic intermediates. Several 2-unsubstituted 1-(alkoxycarbonyl)-l,2-dihydropyridines 1 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…When the ethyl and methyl substituents of the alkynes are reversed, two different products (5m and 5p) were obtained. Although compounds 5 are well set up to undergo a [1,5]sigmatropic shift, we conclude that no [1,5]-sigmatropic shift is taking place under the reaction conditions employed.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…When the ethyl and methyl substituents of the alkynes are reversed, two different products (5m and 5p) were obtained. Although compounds 5 are well set up to undergo a [1,5]sigmatropic shift, we conclude that no [1,5]-sigmatropic shift is taking place under the reaction conditions employed.…”
Section: Resultsmentioning
confidence: 68%
“…As a part of our current studies on the development of new routes in heterocyclic synthesis, 12e15 we report the results of our studies involving the reaction of the zwitterionic intermediates derived from alkyl isocyanides 1 and acetylenic esters 2 with dialkyl 2-(alkyl(aryl)amino)but-2-enedioates [generated in situ from primary alkyl(aryl)amines and acetylenic esters 4], which constitutes a synthesis of highly functionalized 1,2-dihydropyridines (5) in good yields (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comins, et al 8 have reported the asymmetric synthesis of 2-substituted-1,2-dihydropyridines 25 & 26 from N-acyl pyridinium salt 24, which was synthesized via the addition of 3-(triisopropylstannyl)pyridine 22 to an enantiopure chloroformate 23a-b derived from (À)-8-(4-phenoxyphenyl)menthol or (À)-8-phenyl-menthol. The reaction of Nacyl pyridinium salt 24 with different Grignard reagents followed by treatment of the reaction mixture with silica gel containing oxalic acid provided chiral 1,2-dihydropyridines 25 and 26 (Scheme 6, Table 1).…”
Section: Synthesis Of 12-dihydropyridinementioning
confidence: 99%
“…This is the first non-racemic N-acylpyridinium salt prepared in crystalline form. Chiral salts of this type have been prepared in situ and reacted with Grignard reagents to give synthetically useful l-acyl-2-alkyl-2,3-dihydro-4(1H)-pyridinones (Comins, Goehring, Joseph & O'Connor, 1990;Comins & Dehghani, 1991;Comins, Hong & Salvador, 1991;Comins & LaMunyon, 1992;Comins & Killpack, 1993).…”
Section: Commentmentioning
confidence: 99%